Glioblastoma stem cells: new insights in therapeutic strategies. (October 2014) - Goffart, Nicolas; Dedobbeleer, Matthias; Rogister, Bernard
ABSTRACT : Despite notable achievements in glioblastoma diagnosis and treatment, the prognosis of glioblastoma patients remains poor and reflects the failure of current therapeutic modalities. In this context, innovative therapeutic strategies have recently been developed to specifically target glioblastoma stem cells, a subpopulation of tumor cells involved in experimental tumorigenesis and known to be critical for tumor recurrence and therapeutic resistance. The current review summarizes the different trails which make glioblastoma stem cells resistant to treatments, mainly focusing on radio-, chemo- and immunotherapy. This broad overview might actually help to set up new bases for glioblastoma therapy in order to better fight tumor relapses and to improve the patients' prognosis.